Innovative Food Products and Processing - Bhandari, Bhesh R.; Mamat, Hasmadi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the context of the food industry, "Innovative Food Products and Processing" refers to the creation and application of cutting-edge techniques, technologies, and approaches. This vibrant industry covers a broad range of topics, with the aim of enhancing food quality, safety, sustainability, and the consumer experience. This Special Issue, entitled "Innovative Food Products and Processing" provides readers with a wide range of topics and applications in food science and technology, such as the use of food chemistry, biochemistry, fermentation, and microbiology, as well as new contemporary processing and preservation technologies and techniques for effective waste management and green technology for the food processing industry. "Innovative Food Products and Processing" is an excellent resource for food science researchers, food scientists, biochemists, nutritionists, and students. This publication's wide range of topics provides a complete overview of the most recent breakthroughs, cutting-edge technologies, and emerging trends in the food industry.